2013
DOI: 10.1016/j.bbadis.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of lipocalin-2 (LCN2) in acute liver injury suggest a novel function in liver homeostasis

Abstract: Lipocalin-2 is expressed under pernicious conditions such as intoxication, infection, inflammation and other forms of cellular stress. Experimental liver injury induces rapid and sustained LCN2 production by injured hepatocytes. However, the precise biological function of LCN2 in liver is still unknown. In this study, LCN2(-/-) mice were exposed to short term application of CCl4, lipopolysaccharide and Concanavalin A, or subjected to bile duct ligation. Subsequent injuries were assessed by liver function analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 43 publications
9
124
1
Order By: Relevance
“…In addition, the expression of vimentin that indicates increasing amounts of myofibroblasts or fibroblasts is increased after setting of the BDL surgery 20 . The concomitance of inflammation in injured livers are further reflected by increased expression of Lipocalin 2 (LCN2) that is strongly induced during acute and chronic liver injury and evolves hepato-protective effects during acute liver injury 21,22 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…In addition, the expression of vimentin that indicates increasing amounts of myofibroblasts or fibroblasts is increased after setting of the BDL surgery 20 . The concomitance of inflammation in injured livers are further reflected by increased expression of Lipocalin 2 (LCN2) that is strongly induced during acute and chronic liver injury and evolves hepato-protective effects during acute liver injury 21,22 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…2 The presented data corroborate our previous findings that injury-induced up-regulation of hepatic LCN2 has a significant hepatoprotective effect in acute liver injury and that hepatocytes are the major source for hepatic LCN2. 3,4 Furthermore, these data suggest that LCN2 might act as an intrinsic "help-me" sensor that, upon injury, develops an activity necessary to recruit inflammatory cells. In line with this assumption, we observed that lcn2-deficient mice showed a significant lower recruitment of neutrophils and leukocytes, compared to wild-type (WT) animals, when fed with a methionine-choline-deficient (MCD) diet that induces hepatic inflammation and injury (Fig.…”
mentioning
confidence: 99%
“…Other immune modifiers may be drivers for the fibrosis observed in the NGN group. Notably, pretreatment with NVP modified the inflammatory response, dampening the initial M1 inflammatory response to galactosamine presumably via upregulation of lipocalin 2 (Borkham-Kamphorst et al 2013), which pushes macrophage polarization toward the M2 pathway and slightly elevates the apoptotic response. Lipocalin 2 is a soluble secreted protein that binds iron and is protective against hepatic inflammation.…”
Section: Discussionmentioning
confidence: 99%